Organizational Aspects Of System Testing For The Intermediate And Total Control Of Knowledge Of Students - Lizunov, П.П.; Teslay, Ю.М.; Beloshchitskiy, A.O.; Shсherbina, O.A.; Beloshchitska, C.B.; Misnik, Л.Д. (Journal of Information Technologies in Education (ITE), 2009)
The system analysis of organizational problems of working out and application of technologies of computer testing in the higher school is carried out and organizational and functional structures of the automated system of testing are developed for the intermediate and total control of knowledge of students.